Update on novel multiple sclerosis treatments: from dismal defeat to scintillating success - Cree, Bruce; Hartung, Hans-Peter (Current opinion in neurology, 2025)
PURPOSE OF REVIEW: To review novel multiple sclerosis (MS) therapies currently in clinical trials. RECENT FINDINGS: Sixty-seven clinical trials were selected and grouped into the following categories: Bruton's tyrosine kinase inhibitors, remyelinating therapies, immunomodulators, B cell therapies, supplements/microbiome influencers, and cell-directed therapies. Important findings include tolebrutinib's successful trial in nonrelapsing secondary progressive MS that slowed CDP compared to placebo and simvastatin's failure to show an effect on disability in its phase 3 trial. SUMMARY: Multiple strategies are being investigated in MS to address progressive disability, myelin repair, neural protection and treatment refractory disease. Some of these strategies have successfully completed clinical trials giving hope that some of the most vexing aspects of MS will soon have new treatment options.
Keywords: multiple sclerosis; clinical trials; klinické zkoušky jako téma; Bruton's tyrosine kinase; imunologické faktory; Clinical Trials as Topic; lidé; Multiple Sclerosis; Immunologic Factors; remyelination; roztroušená skleróza; disease modifying therapies; Humans